Anti-adipogenic effect of erucin in early stage of adipogenesis by regulating Ras activity in 3T3-L1 preadipocytes. (December 2015) - Chae, Seung Young; Seo, Sang Gwon; Yang, Hee; Yu, Jae Gak; Suk, Su Jin; Jung, Eun Sun; Ji, Hae; Kwon, Jung Yeon; Lee, Hyong Joo; Lee, Ki Won
Highlights: Erucin is an active compound in rocket salad and broccoli, used as functional food. Erucin inhibited adipogenesis of 3T3-L1 preadipocytes at early stage of adipogenesis. ERK signalling pathway was involved in anti-adipogenic effect of erucin. Erucin inhibited Ras activity by decreasing GTP-bound Ras protein. Erucin was shown to have potential to be developed as anti-obesity functional food. Abstract: Erucin is a natural isothiocyanate found in rocket salad and broccoli which are believed to have health benefits including weight control effect and used as a functional food globally. Though anti-cancer effect of erucin has been intensively studied, anti-obesity effect of erucin and its molecular mechanisms have not yet been reported. In this study, we investigated anti-adipogenic effect of erucin in 3T3-L1 preadipocytes and its underlying molecular mechanisms. Erucin inhibited adipogenesis of 3T3-L1 preadipocytes and reduced adipogenic gene expressions. This anti-adipogenic activity of erucin was most effective at early stage of adipogenesis including mitotic clonal expansion (MCE). Fluorescence-activated cell sorter (FACS) analysis and trypan blue assay results showed that erucin induced G1/S arrest and inhibited cell proliferation at MCE stage. Western blot analysis results showed that erucin inhibited extracellular signal-regulated kinase (ERK) signaling pathway by blocking Ras activity. Taken together, these results indicated that erucin inhibits adipogenesis of 3T3-L1 preadipocytes by blocking Ras activity at early stage of adipogenesis.